Alternative Economic Relations under Sanctions - Andrey A. Naryshkin (Современная Европа)
The current international relations crisis caused significant adjustments to the foreign economic activity. During the sanctions confrontation, new restrictions affect more and more tradable sectors, which makes it impossible to maintain previously purchased equipment. It also contradicts legal obligations and the terms of warranty service in the field of spare parts supplies. Buyers represented by government agencies, legal entities and ordinary citizens who trusted Western (mostly European) manufacturers find it hard to deal with the situation. The state is forced to look for ways to supply products and spare parts for previously imported equipment. This process is called “critical import”. Alternative ways of trade development will in fact not only increase the chances to overcome the current international relations crisis, but will also give impetus to variety of possible scenarios for the world trade evolution. This article examines alternative ways of developing international economic cooperation, as well as the development of international relations in the short and medium term prospects. Parallel import is likely to increase during the current crisis and also various trade schemes are likely to develop, namely, barter, deliveries through third countries, the organisation of trading houses.